Chromosoma - Chromosoma (Springer Nature, 2026)
Chromosome Research publishes original research articles, reviews, brief communications, case reports, methodology articles, debates, correspondences and comments from work based on all organisms and encourages submissions in the following areas including, but not limited, to: Chromosomes and linkage to diseases, including cancer cytogenomics. Chromosomes and chromatin function in DNA damage/repair
FI 0.54
Q3
Keywords: Life Sciences; Cell & Molecular Biology; Biología celular; Biología molecular; Acuerdos transformativos; Transformative agreements; Estructura y Función Cromosómica; Dinámica Cromosómica